2020
DOI: 10.26656/fr.2017.4(4).326
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical composition and essential mineral profile, antioxidant and antimicrobial potential of unutilized parts of jackfruit

Abstract: The processing of jackfruit (Artocarpus heterophyllus Lam) yields a considerable amount of bio-waste. Accumulation of this waste is considered a health risk because it is a potential source of air and water pollution. Recycling of the unutilized fruit parts, therefore, reduces the quantity and the impact of the bio-waste released to the environment. The purpose of this study was to determine the phytochemical profile, antioxidant and antimicrobial activities of extracts from three fruit parts (peel, fiber and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 24 publications
0
17
1
1
Order By: Relevance
“…Likewise, Zhang et al [16] reported that, when using 90% methanol for 6 h to extract phenolics, jackfruit peel yields were 4.95, 4.65, and 4.12 times higher than other parts of the fruit such as seeds, pulp, and flake, respectively. However, when comparing the phenolic content obtained from the peel to that from the fiber or core, the one from the fiber is higher (23.28 ± 4.73 mg/g), followed by the peel (17.07 ± 5.16 mg/g), and finally the core (15.68 ± 3.74 mg/g), using a CSE with methanol as solvent followed by 48 h incubation [12]. Sundarraj et al [17] conducted experiments to determine the best temperature and time conditions for pectin extraction with oxalic acid from jackfruit peel, where they found that the best performance results corresponded to 90 • C and 60 min.…”
Section: Conventional Technologiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Likewise, Zhang et al [16] reported that, when using 90% methanol for 6 h to extract phenolics, jackfruit peel yields were 4.95, 4.65, and 4.12 times higher than other parts of the fruit such as seeds, pulp, and flake, respectively. However, when comparing the phenolic content obtained from the peel to that from the fiber or core, the one from the fiber is higher (23.28 ± 4.73 mg/g), followed by the peel (17.07 ± 5.16 mg/g), and finally the core (15.68 ± 3.74 mg/g), using a CSE with methanol as solvent followed by 48 h incubation [12]. Sundarraj et al [17] conducted experiments to determine the best temperature and time conditions for pectin extraction with oxalic acid from jackfruit peel, where they found that the best performance results corresponded to 90 • C and 60 min.…”
Section: Conventional Technologiesmentioning
confidence: 98%
“…The most reported bioactive compounds in jackfruit are phenolic compounds [1] and carotenoids [3]. However, there is evidence of other functional ingredients such as prebiotics including indigestible polysaccharides and oligosaccharides [9,10]; pectin [11]; minerals such as Ca, Fe, K, Mg, and Na [12]; essential fatty acids (EFAs) such as alpha-linoleic and linoleic [13]; and other fatty acids such as palmitic, oleic, stearic, myristic, lauric, capric, and arachidic acids [14], among others. Jackfruit functional ingredients are of great interest owing to their possible applications in the food and pharmaceutical industries, specifically for their health-related benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Ethyl acetate extracts demonstrated the greatest antibacterial action against Xanthomonas axonopodispv. manihotis (Xam) (Adan et al, 2020).…”
Section: Jackfruit (Artocarpusheterophyllus)mentioning
confidence: 99%
“…The peels gave the highest inhibition followed by the fiber while the core gave the least. [20] A. heterophyllus possess antimicrobial activity against some food borne pathogens. Due to the natural origin of this extract, it is more safety for people and environment and low risk for resistance development by pathogenic microorganisms.…”
Section: Antibacterial Activitymentioning
confidence: 99%